The application of radiomics in the diagnosis and evaluation of cognitive impairment related to neurological diseases - Haixing Xiao; Xinyi He; Wei Zhou; Xianghong Guo; Xiuying Cai; Tan Li (Frontiers in Neuroscience)
Cognitive impairment (CI) is common, with diverse underlying causes, symptoms, and imaging features. It often leads to disability and loss of independence. Early diagnosis and assessment of CI are crucial for the prognosis improvement. Conventional diagnostic methods for CI are hindered by subjectivity and imprecision. Radiomics, a sophisticated and objective methodology, has been increasingly utilized in CI in recent times. This article describes the methodology of radiomics and reviews the application of radiomics in the prediction and evaluation of cognitive impairment related to neurological diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), cerebral small vessel disease (CSVD), and stroke. It can provide imaging markers for the early diagnosis and risk stratification of cognitive impairment.